PERANCANGAN IDENTITAS VISUAL LOGOTYPE UNTUK EVENT PEMUTARAN FILM MAHASISWA NON-PROFIT - Meilani Meilani (Jurnal Nawala Visual, 2023)
Designing a Logotype visual identity for non-profit student Film screenings is a form of support for Film students and the public who want to enjoy curated Films every year free of charge. This event provides an experience for Film students and the public to enjoy Film that raises social issues in Indonesia. The screening event has become an alternative distribution channel for Film students to gain connections and experience screening their Films on the big screen. The logo was designed using a secondary data collection method whose results were forwarded to the visual data analysis, brainstorming, and mapping stages to maintain the event's visual identity. The Logotype was successfully implemented in the promotional media for the event in 2019 and 2020 before the Covid-19 Pandemic.